The relationship between community knowledge level and fixed orthodontic treatment performed by non-dentist operators: Hubungan tingkat pengetahuan masyarakat dengan perawatan ortodonti cekat yang dilakukan oleh operator bukan dokter gigi - Pawinru, Ardiansyah S.; Ngadiman, Delicia Anjanette (Makassar Dental Journal, 2025)
This article reports on a study of the relationship between the level of public knowledge and fixed orthodontic treatment perform-formed by non-dentist operators. Subjects were patients who were undergoing orthodontic treatment with non-dentist operators. This study used an analytical observational research method with a cross-sectional research design using consecutive sampling on 96 people. The sample was given a questionnaire to obtain data, namely the knowledge of majority of respondents (52.1%) had a poor level of knowledge regarding fixed orthodontic treatment. Spearman correlation test showed correlation between de-pendent and independent variables with p-value=0.000 and correlation coefficient = -0.557. It is concluded that there is a rela-tionship between knowledge level and orthodontic treatment performed by non-dentist operators.